2017
DOI: 10.1007/s11356-017-0864-7
|View full text |Cite
|
Sign up to set email alerts
|

The association of windmills with conservation of pollinating insects and wild plants in homogeneous farmland of western Poland

Abstract: Loss of suitable seminatural habitats and homogenization of crop types have led to the population decline of pollinating insects in farmland. As these insects support crop production, many practical efforts aim to sustain pollinator diversity which is especially challenging in intensively managed and homogeneous farmland. However, there are ongoing changes of the farmland toward its multifunctionality that includes, for example, wind farm development. Windmills are often built within crops; thus, we examined i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 66 publications
1
12
0
1
Order By: Relevance
“…include openings in forested landscapes, railway and road verges, and industrial areas. (Moroń et al 2014;Blixt et al 2015;Pustkowiak et al 2018). As a notable proportion of natural landscapes was converted into urbanised areas during the previous century (Antrop 2004;Giulio et al 2009), cities are also considered to be important refuges for wild bees.…”
Section: Introductionmentioning
confidence: 99%
“…include openings in forested landscapes, railway and road verges, and industrial areas. (Moroń et al 2014;Blixt et al 2015;Pustkowiak et al 2018). As a notable proportion of natural landscapes was converted into urbanised areas during the previous century (Antrop 2004;Giulio et al 2009), cities are also considered to be important refuges for wild bees.…”
Section: Introductionmentioning
confidence: 99%
“…These results go along with the findings of Urziceanu et al (2018), which indicated that even rare and threatened vascular plants can be found in the neighbourhood of a wind farm in the studied hilly region. Similarly, in a case study conducted in a homogeneous agricultural landscape, Pustkowiak et al (2018) indicated that plant species richness around wind turbines was comparable or even higher to that found in grassland patches or in neighbouring cropland.…”
Section: Discussionmentioning
confidence: 80%
“…Even more recently, the influence of wind 4 farms on vegetation structure at local scale was analysed by performing systematic field surveys. For example, Urziceanu et al (2018) inventoried the presence of rare and vascular plants, while Pustkowiak et al (2018) linked the pollinator diversity to the plant species composition.…”
Section: Introductionmentioning
confidence: 99%
“…No studies show that windmills perform any functions for birds, but some studies show certain positive effects. Uncultivated areas around turbines are usually successively overgrown by herbaceous vegetation, supporting higher diversities of plants and pollinating insects within large arable fields (Pustkowiak et al ., 2018). This may provide birds with additional food and nesting places.…”
Section: Resultsmentioning
confidence: 99%
“…through scattered trees and shrubs) may be key to supporting the movements of organisms through ecological networks and allowing them to adapt their ranges to varying environmental conditions (Manning et al ., 2009). SPELs may also affect adjacent vegetation because they are associated with limited mowing, soil cultivation and the use of chemicals in their immediate vicinity which may contribute to habitat restoration by increasing floristic and structural diversity (López‐Sánchez et al ., 2016; Pustkowiak et al ., 2018). The presence of SPELs may also increase the occurrence of other phenomena such as soil fertilisation from animal droppings (Julig et al ., 2013) and the dispersal of seeds by frugivorous birds (Galindo‐González, Guevara & Sosa, 2000; Luck & Daily, 2003; Athie & Dias, 2016; Guidetti et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%